PERLINDUNGAN HUKUM BAGI PEKERJA SWAKELOLA(PKWT) TERHADAP PERJANJIAN KERJA YANG BERTENTANGAN DENGAN UNDANG UNDANG NO 13 TAHUN 2003 - Khrisna Mulya Sanjaya; Ahmad Sholikhin Ruslie (Gapenas Publisher, 2023)
In the formation of an employment agreement, there is a self-managed work agreement which is also included in the procurement of goods and services, usually in its application it is called a work agreement for a certain time which is in the form of a work contract agreement. In practice, a work agreement issued by the company for employees is still contrary to the labor law when viewed from the formal juridical point of view of a work agreement. In this study, using a normative juridical method with a statutory and conceptual approach, it discusses the application of “Legal protection for self-managed workers against work agreements that are against the law”. The results of the study indicate that the company in making a work agreement appoints a Commitment Making Officer to make an agreement but still the contents of the work agreement are contrary to applicable law, so that with this worker need to be given protection in order to get welfare, especially for self-managed workers